Advancements in operando X-ray techniques for metal additive manufacturing - Kaushalendra K. Singh; Akane Wakai; Atieh Moridi (Communications Materials)
Abstract Operando X-ray techniques have enabled real-time observation and analysis of metal additive manufacturing (AM) processes, providing invaluable insights into solidification mechanisms and melt pool behavior. In this perspective, we present the current state of the art in X-ray diffraction and imaging studies of laser-based metal AM processes, specifically Directed Energy Deposition and Powder Bed Fusion. We explore various data analyses that can be performed with time-resolved data, including phase identification, microstructural evolution, tracking melt pool behavior, and defect formation. Additionally, we highlight the limitations of existing operando studies and provide an outlook on overcoming these challenges.